2009
DOI: 10.1177/1088357609338715
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress and Closeness

Abstract: Mothers of children diagnosed with autism (N = 104) reported higher levels of stress than mothers of typically developing children (N = 342) on 13 of 14 subscales of the Parenting Stress Index. The only scores that did not differ were from the Attachment subscale, which indicates lack of emotional closeness and rather cold patterns of parent-child interaction. Mean Child Domain subscale scores for mothers in the autism group were at the 99th percentile; mean scores on the Attachment subscale were at about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
45
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(66 citation statements)
references
References 37 publications
12
45
3
6
Order By: Relevance
“…Our finding was consistent with previous studies that found parents of individuals with learning disabilities to be under considerable stress (5)(6)(7)(8)10). Higher stress levels in caregivers might increase susceptibility to stress-induced illness and affect the adjustment to taking care of their child with learning disability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding was consistent with previous studies that found parents of individuals with learning disabilities to be under considerable stress (5)(6)(7)(8)10). Higher stress levels in caregivers might increase susceptibility to stress-induced illness and affect the adjustment to taking care of their child with learning disability.…”
Section: Discussionsupporting
confidence: 93%
“…Previous works showed that the parenting stress level is higher in parents of children with learning disabilities than in parents of normal children (5)(6)(7)(8) …”
Section: Introductionmentioning
confidence: 99%
“…Parents of children with ASD experience higher levels of parenting stress than parents of typically developing children (e.g., Duarte et al 2005;Hayes and Watson 2012;Hoffman et al 2009;Rao and Beidel 2009) as well as parents of children with other developmental disabilities (e.g., Estes et al 2009Estes et al , 2012Schieve et al 2007Schieve et al , 2011. This is concerning given that high levels of parenting stress are associated with diminished child outcomes over time following intervention (Osborne et al 2008a, b).…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…Raising a child with autism or another developmental disability is often stressful for parents and can affect sibling adjustment as well. Hoffman, Sweeney, Hodge, Lopez-Wagner and Looney (2009) found parental stress to be higher among mothers of children with autism compared to both mothers of typical children and mothers of children with developmental delays. Children with an intellectual disability often have higher levels of behavior problems than children without an intellectual disability (Baker et al, 2003).…”
mentioning
confidence: 92%